Empowering community movement: empirical evidence - Abu Bakar, Aisyah; Mohamed Osman, Mariana; Abdullah, Muhammad Faris (Malaysian Institute Of Planners, 2019)
The living environment in which humans dwell in and are surrounded by, and thus include the immediate built environment is fertile ground for personal development leading to community advancement. Issue: Ample amount of studies have been carried out on the influence of personal empowerment (PE) on community movement (CM). Little attention were given to the empirical evidence of the impact of PE on CM. Purpose: This paper sets out to confirm the statistical predictability of CM based on PE. Approach: Multiple Correlation and Multiple Linear Regression were executed to assess linear associations and parameters of linear equations to predict CM components based on PE items. Findings: Majority of PE items were significant predictors of CM components and ‘setting goals and striving to meet goals’ was the strongest predictor of CM.